Identidade social e autoestima de travestis, homens e mulheres trans e transgêneros : a influência do apoio social - Silva, Bruno de Brito (2016)
This master thesis consists of four studies, two of theoretical character and two that have analytical and quantitative approach in order to investigate the social identity and self-esteem of transvestites and transwomen and transmen, as well as knowing the influence and role of social support network, formed by family, love relationships and the LGBT community, in the constitution of these. Studies 1 and 2 theorized on how are these phenomena among transgender, being the first a review of social identity and social support and the second, a systematic review of the literature on self-esteem with this part of the population. It was highlighted the importance of social support for the successful development and good formation of self-esteem and social identity in transgender. Study 3 adapted and investigated evidence of validity and reliability of Need for Identification Scale (nID), offering a reliable and valid measure in the measurement of social identity construct. Finally, the study 4, explored the variables mentioned above and their correlations in transgender through an online questionnaire including scales: of the body Identity questionnaire, of the questionnaire Brazilian Youth, nID Scale, validated in study 3, the ESSS and the marital satisfaction GRIMS Scale. There were 203 participants from all regions of the country, of which 34.8% were transvestites and transwomen. It was found that the bigger the family support, the higher the self-esteem, and the fact of being in hormone therapy, increasing age and satisfaction with social support, predicted greater social identification for the participants towards the identity and expressed gender belonging group. It also alert to the need for social acceptance of transgender modes/ways of existence in society.